Tracing the Jerusalem Code Volume 1: The Holy City Christian Cultures in Medieval Scandinavia (ca. 1100-1536) - Aavitsland, Kristin B.; Bonde, Line M. (De Gruyter, 2021)
With the aim to write the history of Christianity in Scandinavia with Jerusalem as a lens, this book investigates the image - or rather the imagination - of Jerusalem in the religious, political, and artistic cultures of Scandinavia through most of the second millennium. Jerusalem is conceived as a code to Christian cultures in Scandinavia. The first volume is dealing with the different notions of Jerusalem in the Middle Ages.